KEMAMPUAN BAHASA INDONESIA BAGI PENUTUR ASING MAHASISWA THAILAND SELATAN MATERI PERKENALAN DI UNIVERSITAS MUHAMMADIYAH JAKARTA - Susanti, Amalia; Septiandari, Dinda; Khaerunnisa, Khaerunnisa (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This study aims to determine and describe the Indonesian vocabulary of Thai students in semester 1 at the University of Muhammadiyah Jakarta. The method used in this study is the content analysis method. The data of this study are in the form of vocabulary obtained from the results of interviews with Thai students in semester 1 at the University of Muhammadiyah Jakarta with learning carried out by Thai students. Data collection techniques used listening techniques and note-taking techniques. The results of the study showed that from the results of the data analysis obtained, students were able to use vocabulary well, such as: 1) Introducing names, 2) Mentioning place of residence, 3) Mentioning age, 4) Mentioning study programs being taught, 5) introducing friends from other study programs, 6) Distinguishing the words female student and student, 7) Being able to ask when they don't understand, 8) Being able to answer questions according to context, 9) Being able to introduce friends next to them, 10) Being able to distinguish the pronunciation of the words female student and student, In addition, students can also understand and answer questions through media such as WhatsApp, provide information about other people, ask about differences in origin and place of residence, and give permission at the request of the interlocutor. Overall, the vocabulary skills of Thai students at Muhammadiyah University of Jakarta show good and relevant results in the context of learning Indonesian.